Exploring Brain Size Asymmetry and Its Relationship with Predation Risk Among Chinese Anurans - Chuan Chen; Ying Jiang; Yiming Wu; Lingsen Cao; Wenbo Liao (Biology)
Brain size asymmetry differs considerably across species, including humans, vertebrates, and invertebrates. The subtle structural, functional, or size differences between the two brain sides are associated with processing specific cognitive tasks. To evaluate the differences between the sizes of the left and right sides of the whole brain and brain regions and the effect of predation risk (i.e., snake density) on brain size asymmetry among Chinese anurans, we compared the differences between the left and right hemisphere sizes of the whole brain and brain regions among anuran species and analyzed the correlations between the predation risk and size asymmetry index of the brain and brain regions. We found that when one side of the brain was consistently larger than the other, there was a significant difference between the sizes of the left and right sides of the brain and brain regions, displaying directional asymmetry of the whole brain and brain regions. We also found that total brain size was positively correlated with the size asymmetry index of the olfactory bulb and optic tecta when the left hemispheres of the whole brain and brain regions were larger than the right ones. Meanwhile, the index of telencephalon size asymmetry was positively correlated with predation risk when the right hemispheres of the brain and brain regions were larger than the left ones. However, there were non-significant differences between the sizes of the left and right sides of the brain and brain regions across 99 species of anurans. Our findings suggest that an increased predation risk linked to sociality is likely to drive an increase in right telencephalon size.